Long-Term Bone Scintigraphy Results After Intravenous Zoledronate in Paget’s Disease of Bone - Reid, Ian R.; Maslowski, Katherine (Calcified tissue international, 2017)
Zoledronate produces long-term normalization of biochemical markers in Paget’s disease but whether this implies the absence of active disease is unknown. We have determined whether bone scintigraphy, a more sensitive index of disease activity, is also normalized ≥5 years after treatment with zoledronate. A consecutive case series of 11 individuals with Paget’s disease treated with zoledronate 5 mg ≥5 years previously is reported. Eight patients received a single zoledronate infusion and were assessed 55–120 months later. Bone scintigraphy showed no evidence of active disease in four of these patients, and there was minimal residual disease activity in the other four. Three other patients required second infusions because of evidence of ongoing disease activity. In two of these, scintigraphy was normal ~90 months after their second infusions. In the third, further follow-up is not available. Procollagen-I N-terminal propeptide and total alkaline phosphatase were normal in all subjects at the time of bone scintigraphy. This case series confirms the high rate of response of Paget’s disease to zoledronate, demonstrates the much greater sensitivity of scintigraphy compared with biochemical markers in detecting ongoing disease activity, and indicates that about one-third may be scintigraphically “cured” after one infusion; one-third have scintigraphically trivial disease activity subsequently, and the balance may require a second infusion. Scintigraphic “cure” is achievable after second infusions. Scintigraphy has an important place in the long-term management of Paget’s patients following zoledronate, and should guide follow-up decisions in those with normal biochemical markers.